1983
DOI: 10.1111/j.1365-2621.1983.tb03503.x
|View full text |Cite
|
Sign up to set email alerts
|

Pectin‐Protein Interaction in Tomato Products

Abstract: The pH influenced the viscosity of a model system of tomato product which consisted of citrus pectin and bovine serum albumin. The viscosity change was completely reversible depending on the pH. The same pH effect was observed in tomato products. Since the amino acid compositions of proteins suggest that the electrostatic property of water-soluble protein fraction from tomato juice can be similar to that of bovine serum albumin, the comparison of pH effects indicates that pectin-protein interaction may be invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 9 publications
5
28
0
Order By: Relevance
“…, Ruth Cardinaels (3,4) , Lucy Bialek Abstract Rheological properties of cell wall suspensions strongly depend on particle size and particle-particle interactions. In the present study, an experimental method was developed to study the effect of particle elasticity and electrostatic interactions on the rheological properties of cell suspensions.…”
Section: Take Down Policymentioning
confidence: 99%
See 1 more Smart Citation
“…, Ruth Cardinaels (3,4) , Lucy Bialek Abstract Rheological properties of cell wall suspensions strongly depend on particle size and particle-particle interactions. In the present study, an experimental method was developed to study the effect of particle elasticity and electrostatic interactions on the rheological properties of cell suspensions.…”
Section: Take Down Policymentioning
confidence: 99%
“…Ashwin K Sankaran (1,2), Jaap Nijsse (1) , Ruth Cardinaels (3,4) , Lucy Bialek (1) , Avi Shpigelman (2) , Marc Hendrickx (2) , Paula Moldenaers (3) Effect of enzymes on serum and particle properties of carrot cell suspensions Ashwin K Sankaran (1,2) , Jaap Nijsse (1) , Ruth Cardinaels (3) , Lucy Bialek (1) , Avi Shpigelman (2) , Marc Hendrickx (2) , Paula Moldenaers (3) and Ann M. Van Loey (2,*) the date of receipt and acceptance should be inserted later Abstract Rheological properties of cell wall suspensions strongly depend on particle size and particle-particle interactions. In the present study, an experimental method was developed to study the effect of particle elasticity and electrostatic interactions on the rheological properties of cell suspensions.…”
Section: Effect Of Enzymes On Serum and Particle Properties Of Carrotmentioning
confidence: 99%
“…The shape of the curves for sera obtained by the either steam injection or HTS method was not a linear relationship and differed from the sera obtained by kettle or Waring blender methods. Takeda and Nelson [16] reported that the tomato paste was produced by hot-break with a kneading action, the relationships between consistency, serum viscosity, and PPT ratio would be different from those produced by traditional process methods.…”
Section: Effect Of Physical Properties On the Tomato Seramentioning
confidence: 99%
“…The resultant precipitates (i.e., solids) were weighed, and the precipitate weight ratio (PPT) was calculated for each sample. This method was followed from Takada and Nelson [16], Barrett, et al [12]. Average values from triplicate measurements were reported.…”
Section: Determination Of Serum Viscositymentioning
confidence: 99%
See 1 more Smart Citation